Address Terms Used In Relation To Social Identity In Mamben Daya Village - Rahmani, Neli; Nurtaat, Lalu; Kamaludin, Kamaludin (Journal of Authentic Research, 2026)
The Sasak community of Gelumpang Hamlet in Mamben Daya Village, East Lombok, possesses a rich and culturally embedded system of address terms that reflects core values such as age hierarchy, social status, and communal solidarity. However, modernization and increasing contact with Indonesian and global languages have begun to influence the linguistic practices of younger speakers. This study aims to analyze the forms, functions, and factors influencing the use of address terms in this community. This study employed a qualitative sociolinguistic case study design. Data were collected through naturalistic observation, audio-recorded everyday conversations, and semi-structured interviews with Sasak speakers. Data analysis was conducted using content analysis and discourse analysis, involving transcription, coding, categorization, and sociolinguistic interpretation. The findings reveal that Sasak address terms consist of nominal and pronominal forms that are systematically used to index power, politeness, and social solidarity. Age and social status were identified as the most influential factors in address selection, while intimacy and situational context further shape usage patterns. Theoretically, these findings contribute to sociolinguistic studies by demonstrating how address systems function as mechanisms for negotiating social relationships. Practically, this research supports the documentation and preservation of Sasak linguistic and cultural practices in the face of social change. Nevertheless, this study is limited to a single community with a relatively small number of participants and a restricted observation period; therefore, the findings should be interpreted with caution and not overgeneralized.